2018
DOI: 10.1016/bs.mie.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Robust Production, Crystallization, Structure Determination, and Analysis of [Fe–S] Proteins: Uncovering Control of Electron Shuttling and Gating in the Respiratory Metabolism of Molybdopterin Guanine Dinucleotide Enzymes

Abstract: [Fe–S] clusters are essential cofactors in all domains of life. They play many biological roles due to their unique abilities for electron transfer and conformational control. Yet, producing and analyzing Fe–S proteins can be difficult and even misleading if not done anaerobically. Due to unique redox properties of [Fe–S] clusters and their oxygen sensitivity, they pose multiple challenges and can lose enzymatic activity or cause their component proteins to be structurally disordered due to [Fe–S] cluster oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 183 publications
(243 reference statements)
0
10
0
Order By: Relevance
“…Here, we have shown that there is a single Fe–S cluster in four-subunit Pol ϵ and that this cluster is bound to the Cys-motif (CysX) at the base of the P-domain in the catalytic subunit, Pol2. Fe–S clusters have been reported to stabilize protein structures and subunit interactions, but also to regulate substrate binding and/or catalysis in a redox state-dependent manner (27–33). In the case of the two replicative eukaryotic polymerases, Pol δ and Pol ϵ, there are clear differences when comparing the function of their Fe–S clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have shown that there is a single Fe–S cluster in four-subunit Pol ϵ and that this cluster is bound to the Cys-motif (CysX) at the base of the P-domain in the catalytic subunit, Pol2. Fe–S clusters have been reported to stabilize protein structures and subunit interactions, but also to regulate substrate binding and/or catalysis in a redox state-dependent manner (27–33). In the case of the two replicative eukaryotic polymerases, Pol δ and Pol ϵ, there are clear differences when comparing the function of their Fe–S clusters.…”
Section: Discussionmentioning
confidence: 99%
“…To accelerate biochemical studies of [Fe-S] proteins, genes encoding proteins of interest are often heterologously expressed in engineered E. coli strains designed for overproduction of proteins. A major challenge in the field is to obtain large enough quantities of proteins at high concentrations that are also maximally occupied with [Fe-S] clusters (34). Increasing the expression levels of housekeeping Isc pathway imparts variable improvement in [Fe-S] cluster protein yields (8,13,20,34).…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge in the field is to obtain large enough quantities of proteins at high concentrations that are also maximally occupied with [Fe-S] clusters (34). Increasing the expression levels of housekeeping Isc pathway imparts variable improvement in [Fe-S] cluster protein yields (8,13,20,34). However, to our knowledge, a similar approach has not been examined for the Suf pathway despite it being the sole pathway for [Fe-S] biogenesis in many organisms.…”
Section: Introductionmentioning
confidence: 99%
“…To accelerate biochemical studies of [Fe-S] proteins, genes encoding proteins of interest are often heterologously expressed in engineered E. coli strains designed for overproduction of proteins. A major challenge in the field is to obtain large enough quantities of proteins at high concentrations that are also maximally occupied with [Fe-S] clusters (17) to enable spectroscopic and structural studies. Increasing the level of the housekeeping Isc pathway imparts variable improvement in [Fe-S] cluster protein yields (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…A major challenge in the field is to obtain large enough quantities of proteins at high concentrations that are also maximally occupied with [Fe-S] clusters (17) to enable spectroscopic and structural studies. Increasing the level of the housekeeping Isc pathway imparts variable improvement in [Fe-S] cluster protein yields (17)(18)(19)(20). However, to our knowledge, a similar approach has not been examined for the Suf pathway despite it being the sole pathway for [Fe-S] biogenesis in many organisms.…”
mentioning
confidence: 99%